Need for additional anesthesia after single injection spinal analgesia for labor: a retrospective cohort study. (November 2019) - Sharpe, E.E.; Kim, G.Y.; Vinzant, N.J.; Arendt, K.W.; Hanson, A.C.; Martin, D.P.; Sviggum, H.P.
Highlights: The median reduction in pain score was 9 (0–10 scale) after labor spinal analgesia. Of 429 women receiving spinal analgesia, 14% later needed anesthesia. Primiparity, induction and lower cervical dilation increased risk of anesthesia. Two patients (0.5%) ultimately needed general anesthesia for cesarean delivery. Abstract: Background: There is little information about the use and efficacy of single injection spinal blocks for labor analgesia; specifically, how frequently subsequent analgesia or anesthesia is needed. This study determined how frequently an additional anesthetic intervention was needed in women who received single injection spinal analgesia. Methods: This retrospective study examined electronic medical records to find all single injection spinal analgesic blocks for labor analgesia over a 14-year (2003–2016) period. Patient and block characteristics and patient outcomes were recorded. The primary outcome was need for an additional anesthetic intervention following single injection spinal for labor analgesia. Results: Four-hundred-and-twenty-eight patients received single injection spinal blocks for labor and 60 (14.0%) needed an additional anesthetic either for labor analgesia (n=49) or an unexpected procedure (n=11). Two of these (0.5%) required general anesthesia. Parity of zero (nulliparous), a low cervical dilation at the time of the spinal injection, and induction of labor status, were associated with an increased risk of needing an additional anesthetic intervention. Conclusions: This retrospective review provides evidence that single injection spinal anesthesia may be used for multiparous women with spontaneous labor and more advanced cervical dilation.